Banganubade Meghdut : Bicchurita Punapath (বঙ্গানুবাদে মেঘদূত : বিচ্ছুরিত পুনঃপাঠ) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
In the 4th century AD, the great poet Kalidasa composed 'Meghadutam' in Sanskrit, in Mandakranta rhythm. In this text, a Yaksha, exiled to the Ramgiri mountain for dereliction of duty, sent a cloud as a messenger to his solitary lover at Alkapuri on the arrival of monsoons. The famous poet Rabindranath Tagore observed the suffering of seperation of all people in the midst of the Yaksha's wretchedness. Even in 21st century, this poetry has great effects on the reader's mind in various ways. The ‘Meghadutam’ has been written and studied in Bengali language in two ways mainly. The initial practice is a direct translation of the Sanskrit poem. On the other hand, modern poets have adopted Meghadutam's style and have taken a vow to write ‘Uttar-Meghadutam’ in their own way. In the present research article, we discussed about the various Bengali translations of ‘Meghadutam’.            Translation is no longer treated as a mere imitation of the original text or the translator a mere copyist. According to modern translation studies, translation becomes a new creation when the translator interprets the topic, mood, and symbols of the source text and transforms it into the language and culture of the target text. The translated text itself becomes a new text or reproduction of the original work. It’s no longer called as a reflection of the original text, rather it can be called as refraction. André Lefevere developed the idea of translation as a form of rewriting.             In 1850, Meghdoot's Bengali translation was started by Anandachandra Shiromani. From then till now, more than thirty-six Bengali translations have been found. The translation of any ancient literature makes that a part of contemporary living literature. Translation is not only as a form of communication but also as continuity. For the purpose of detailed discussion two translated texts in poetry form, have been selected from the vast collection of Bengali ‘Meghdoot’. The first text is 'Meghdoot' translated by Dwijendranath Tagore [publication year: 1859], the other is 'Meghdoot' by Buddhadeva Bose [publication year: 1957]. Translations do not only represent the original text; but also show the era of the translator and the personality of the reproducer. Through a comparative discussion of two works translated almost a hundred years apart, we will try to understand how the two translators managed to create distinct new texts while following the original.
Keywords: Translation studies; Source text; Target Text; Reproduction; Refraction; Rewriting